PENGARUH METODE PENGGERUSAN TABLET VITAMIN C TERHADAP KADAR BAHAN AKTIF - Damaranie Dipahayu Dipahayu; Silfiana Nissa Permatasari (Jurnal Kimia Riset, 2019)
One form of prescription service is preparing pulveres dosage form. Pulveres are generally obtained from the grinding technique of several tablet preparations and mixing them. The common grinding technique is manually using a mortar-stamper and a blender (pulverization machine). The use of a blender is considered more practical and shortens the time but the heat of blender can reduce levels of active ingredients which is unstable of high temperature. This study aims to determine whether the manual grinding method and blender of vitamin C tablets will affect the levels of active ingredients. Determination of levels of active ingredients of vitamin C tablets that was crushed by the HPLC method. Based on the results of the study, it is known that the levels of manually crushed vitamin C are 191,919 mg and 192,872 mg, while the blended vitamin C levels are 181,204 mg and 179,886 mg. The conclusion of this study shows that the blender method can cause a decrease in vitamin C levels greater than the manual method however, both methods can still maintain the availability of ascorbic acid content in the concentration range of 90% - 110.0%.